Impact of ERP System Implementation on Operational and Financial Efficiency in Manufacturing Industry - Titis Sri Wulan; Putri Wahyu Novika; Elmi Nurvianti; Feby Arma Putra (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to analyze the effect of implementing an ERP (Enterprise Resource Planning) system on operational and financial efficiency in the manufacturing industry. ERP systems are known to simplify business processes and improve efficiency, but their impact varies across companies. Using the linear regression method, this study measures the effect of variables such as production time reduction, inventory management, productivity improvement, cash flow improvement, and operating cost reduction on firm efficiency. Data was obtained from ten manufacturing companies in Indonesia that implemented ERP systems in the period 2016-2021. The results showed that all independent variables had a positive and significant effect on operational and financial efficiency. Regression coefficients show that reduced production time and improved inventory management contribute significantly to efficiency, with coefficients of 0.452 and 0.328, respectively. Increased productivity, improved cash flow, and reduced operating costs also showed a positive influence with coefficients of 0.378, 0.414, and 0.391. These findings indicate that ERP system implementation can effectively improve operational and financial efficiency in the manufacturing sector, contributing to cost reduction and productivity improvement. This research is expected to provide insights for companies considering ERP implementation to improve their operational and financial performance.